A gestão do conhecimento nos processos do Departamento de Almoxarifado da UFSCar - Silva, Jônatas Rodrigues da (2015)
Knowledge management is the orderly activity that an organization conducts to appropriate the known knowledge, register and catalog it, and make it available to the entire organization.The management, creation, and dissemination of knowledge is important for any organization. The present descriptive investigation, through a case study, analyzed the actual knowledge in the processes performed by the Warehouse Department at the Federal University of São Carlos (UFSCar), and has identified the tacit and explicit knowledge, and proposed a model for the Management of knowledge at UFSCar. The main theoretical reference was the theory of knowledge creation proposed by Japanese professor Ikujiro Nonaka.